Compressive behavior of heat-damaged square concrete prisms confined with basalt fiber-reinforced polymer jackets. (1st September 2021) - Song, Jiang; Gao, Wan-Yang; Ouyang, Li-Jun; Zeng, Jun-Jie; Yang, Jian; Liu, Wei-Dong
Highlights: Compressive behavior of heat-damaged square concrete columns confined with BFRP jackets was investigated. Effects of exposure temperature and BFRP jacket layers on the experimental results were studied. The confinement mechanism of BFRP-confined heat-damaged concrete was discussed. The accuracy of typical confinement models for FRP-confined heat-damaged concrete was examined. Abstract: Externally bonded fiber-reinforced polymer (FRP) composites are increasingly used to confine concrete columns as an effective strengthening technique. During the past two decades, a significant research effort has focused on the performance of FRP-strengthened concrete structures under fire exposure. However, there is still a lack of research on the structural behavior of heat- or fire-damaged concrete structures repaired with FRP composites. This paper presents the results of the first-ever experimental study on the compressive behavior of heat-damaged square concrete prisms that are either unconfined or confined by a promising type of FRP composites made of basalt fibers. A total of 51 specimens were prepared and tested under axial compression. The design variables included the heat-induced damage levels of concrete prisms after exposure to various elevated temperatures (200, 400, 600 and 800 °C) and the layers of basalt FRP (BFRP) jackets (2-, 3- and 4-layer) used for strengthening. The failure modes, compressive strengths, ultimate axial strains, axial stress–strain curves, and axial strain-to-hoop strain relationships of the specimens were investigated and compared. The external confinement of the BFRP jackets was proved to be effective in enhancing the strength and deformation capacities of heat-damaged concrete with a square cross-section. The strength growths and the ultimate axial strains of the BFRP-confined heat-damaged square concrete prisms were improved with the increase in the exposure temperature or the number of BFRP jacket layers. Two typical concrete confinement models were then modified by taking the residual mechanical properties of concrete into account to predict the compressive behavior of the BFRP-confined heat-damaged concrete with a square cross-section. The comparisons between the test results and the model predictions are presented, and the accuracy of the concrete confinement models are examined and discussed.